2012
DOI: 10.1371/journal.pone.0048922
|View full text |Cite
|
Sign up to set email alerts
|

Tetrahymena: An Alternative Model Host for Evaluating Virulence of Aeromonas Strains

Abstract: An easier assessment model would be helpful for high-throughput screening of Aeromonas virulence. The previous study indicated the potential of Tetrahymena as a permissive model to examine virulence of Aeromonas hydrophila. Here our aim was to assess virulence of Aeromonas spp. using two model hosts, a zebrafish assay and Tetrahymena-Aeromonas co-culture, and to examine whether data from the Tetrahymena thermophila model reflects infections in the well-established animal model. First, virulence of 39 Aeromonas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…Seven virulent A. hydrophila strains (NJ-35, XY-16, NJ-34, CS-43, NJ-1, XX-14, and NJ-37), and five avirulent A. hydrophila strains (NJ-28, JH-19, NJ-3, CS-34, and JH-17; Pang et al, 2012), were used in this study (Table 1). The nucleotide sequence of the complete genome of NJ-35 has been deposited in GenBank (accession number CP006870).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven virulent A. hydrophila strains (NJ-35, XY-16, NJ-34, CS-43, NJ-1, XX-14, and NJ-37), and five avirulent A. hydrophila strains (NJ-28, JH-19, NJ-3, CS-34, and JH-17; Pang et al, 2012), were used in this study (Table 1). The nucleotide sequence of the complete genome of NJ-35 has been deposited in GenBank (accession number CP006870).…”
Section: Methodsmentioning
confidence: 99%
“…Then, 5000:1 co-cultures of A. hydrophila and T. thermophila were used to investigate their interaction (Pang et al, 2012). Before co-culture, T. thermophila SB210 with an initial inoculum of 10 3 cells/mL was grown in 50 mL of SPP medium at 28°C for 36 h, when the cultures entered stationary phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hcp secretion was found to be strongly induced by 30 low temperature in A. hydrophila. Immunoblot analysis demonstrated that Hcp is 31 conserved among A. hydrophila strains of different origins. The vaccination with 32 recombinant Hcp resulted in an increased survival (46.67%) in common carp during a 33 10-day challenge time compared to non-vaccinated fish (7.14%).…”
mentioning
confidence: 99%